2013
DOI: 10.1002/etc.2420
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cylindrospermopsis raciborskii (cyanobacteria) on the swimming behavior of Daphnia (cladocera)

Abstract: The present study aimed to test the effects of raw water samples from a eutrophic reservoir and of a saxitoxin-producing strain of Cylindrospermopsis raciborskii on the swimming behavior of 2 key herbivore species of Daphnia. Two complementary approaches were used, acute bioassays and behavioral assays using an automated movement tracking system for measuring the following activity parameters: swimming time, resting time, distance traveled, and mean velocity. In both assays, animals were exposed to field sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…The paralysis effect observed in D. similis and M. micrura in the acute assays with single exposures to the CYRF strain is in agreement with previous studies using the same cladoceran species and has been attributed to the presence of saxitoxins in this strain . Nevertheless, by using living cells and not pure toxins, effects of compounds other than microcystins and saxitoxins cannot be ruled out.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The paralysis effect observed in D. similis and M. micrura in the acute assays with single exposures to the CYRF strain is in agreement with previous studies using the same cladoceran species and has been attributed to the presence of saxitoxins in this strain . Nevertheless, by using living cells and not pure toxins, effects of compounds other than microcystins and saxitoxins cannot be ruled out.…”
Section: Discussionsupporting
confidence: 91%
“…Contrary to the studies of Ferrão-Filho et al [10,11], Soares et al [20] attributed these effects not to toxicity, but to low nutritional value and interference with feeding, leading to energy limitations. In the present study, we did find positive clearance rates in all diets, although they were lower in cyanobacteria than in green algae in both single and mixture treatments.…”
Section: Cyrfmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous reports identified that a concentration of 1.37 ng L −1 STX caused a 50% reduction in the motility of D. similis after a 2-h exposure (Ferrão-Filho et al 2014). Even smaller concentrations (0.24 ng L −1 ) inhibited natatory movements of D. pulex (Costa et al 2013).…”
Section: Resultsmentioning
confidence: 86%
“…Vilar, personal communication). This cyanobacterium is considered potentially toxic to zooplankton, especially to cladocerans (Ferrão-Filho et al 2014). The presence of these potentially toxic cyanobacteria is a common feature in Brazilian Northeast Reservoirs (Dantas et al 2011, Almeida et al 2012).…”
Section: Discussionmentioning
confidence: 99%